Molecular Spectroscopy and Molecular Docking Studies on (E)-1-(4-Bromobenzylidene) Thiourea - Das, Shyamal; Bharanidharan, S.; Dhandapani, A. (Journal of New Developments in Chemistry, 2018)
The organic molecule (E)-1-(4-bromobenzylidene)thiourea (BBTU) have been synthesized and characterized using FT-IR and FT-Raman spectral studies. The quantum chemical calculations of BBTU have been studied using DFT/B3LYP/6-31G(d,p) level of theory. The stable conformer is identified by the potential energy surface scan. The complete vibrational assignments were performed on the basis of PED analysis with the help of SQM method. NBO analysis was carried out to explore the various conjucative/hyperconjucative interactions within the molecule and their second order stabilization energy. The NLO activity of BBTU is calculated and compared with the standard Urea molecule. The energies of the FMOs are used for the determination of global reactivity descriptors. The electrophilic and nucleophilic charge sites were identified by the molecular electrostatic potential mapped surface. The molecular docking of BBTU is carried out with the receptors of 3U2D and 1JIJ to screen the bacterial activity.
Keywords: DFT Study; FT-IR; FT-Raman; NLO; NBO; Molecular Docking.